(3EYdGe GdSGFdjf Yf cJH SjO GdeQSdjfs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg EYdGe GdSGFdjf hgh eTJed Ydi CHhGH , GdChd aj cJGH GdfHj Udj Gddg Ydjg hSde Edi GdfLGTj s
(3BNQgG (B:s
(3Ydjge CMO Cf jZdHge QShd HYKI YeQh Hf CejI Edi GdfLGTi aCNP cJGH QShd Gddg Udi Gddg Ydjg hSde hhVYg Ydi Yjfjg s
(3Vef eLehY s
(3GfXQ Qbe (B50 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B368 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B495 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B37 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs